Voiding Behavior and Efferent Bladder Function Altered in Mice Following Social Defeat but Not Witness Trauma - West, Eliza G.; Sellers, Donna J.; Chess-Williams, Russ; McDermott, Catherine (Frontiers in Physiology, 2020)
Psychological stress is associated with bladder dysfunction, however the local bladder mechanisms affected are not well understood. This study aimed to determine how psychological stress, caused by social defeat or witness trauma, affects voiding behavior and bladder function. Pairs of male C57Bl/6J mice were placed in a custom-made plexiglass chamber with an aggressor ARC(S) mouse for 1 hour/day for 10 days. The social defeat mouse was in physical contact with the aggressor, while the witness was physically separated but could observe interactions between its cage-mate and the aggressor. Age matched control pairs were used for comparison. Voiding analysis was conducted periodically over the 10 days. An ex vivo whole bladder preparation was used to assess functional changes after the period of stress. Plasma corticosterone levels were significantly increased by both social defeat and witness trauma stress when compared to unstressed controls. Voiding analysis revealed a significant decrease in voiding frequency in the social defeat group compared to control animals, indicating an altered voiding phenotype. Witness trauma did not alter voiding behavior. Bladder contractile responses to cholinergic stimulation were not significantly altered in either stress group, nor was relaxation to the beta-adrenoceptor agonist isoprenaline. However, nerve evoked contractile responses were significantly increased at all frequencies in bladders from social defeat but not witness trauma mice. Purinergic contractile responses were also significantly enhanced in this group. Social defeat also resulted in increased urothelial acetylcholine release during bladder distension, with no change in ATP release. In conclusion, functional bladder changes are dependent upon stressor type. Enhanced urothelial acetylcholine may desensitize bladder sensory nerves, which, coupled with more efficient voiding contractions due to enhanced nerve-mediated and purinergic detrusor responses, may account for the altered voiding phenotype observed. This study reports a male model of social defeat stress with reduced urinary frequency, with no voiding changes observed in the witness.